POLA KOMUNIKASI ORGANISASI PADA PT AMBARA KARYA PRADANA (HONDA PRADANA SAWANGAN) DI MASA PANDEMI - Rainy, Dewintha; Rahayu, Muthia (Reputasi : Jurnal Public Relations, 2024)
This study discusses problems with communication patterns within corporate organizations, namely communication patterns between superiors and subordinates in communication caused by communication patterns during a pandemic. This research wants to know how the pattern of communication at PT. Ambara Karya Pradana (Honda Pradana Sawangan) during the pandemic. The theory in this study uses organizational communication theory that communication is a liaison process between superiors and subordinates to overcome communication problems within the company. The paradigm in this study uses post-positivism with a qualitative descriptive approach. Data collection techniques use primary and secondary data. Primary data obtained by in-depth interviews with informants. Secondary data obtained from the literature books, journals and direct observation results. The results of the study show that the communication patterns that were formed within the company's organization during the pandemic period, namely switching from the communication patterns of superiors and subordinates which previously applied face-to-face and directly, are currently changing to online or online using social media, but online communication is a separate problem from the messages conveyed. less effective delivered from superiors and subordinates.